The Job Demands-Resources model: Further evidence for the buffering effect of personal resources - Maxime A. Tremblay; Deanna Messervey (SA Journal of Industrial Psychology, 2011)
Orientation: In work and organisational psychology, the adverse effects of job demands have often been demonstrated empirically for various indicators of job strain. Research purpose: Using the Job Demands-Resources (JD-R) model as a theoretical framework, the present study examined the role of compassion satisfaction, conceptualised as a personal resource, in buffering the relationship between job demands and job strain.